2017
DOI: 10.12669/pjms.334.13112
|View full text |Cite
|
Sign up to set email alerts
|

A rare case of Ralstonia mannitolilytica infection in an end stage renal patient on maintenance dialysis during municipal water contamination

Abstract: Ralstonia mannitolilytica is a gram negative soil bacterium. Ralstonia infection though rare, has become the emerging nosocomial pathogens in hospital settings. Various clinical manifestations had been described as well as the mode of transmission. Despite its low virulence factor, it is able to survive under harsh condition and this may potentially cause significant morbidity and mortality especially in immunocompromised patients. Outbreak of Ralstonia mannitolilytica infections in the hospital are typically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 8 publications
1
23
0
Order By: Relevance
“…In the present study, the genus Ralstonia (class Betaproteobacteria) was detected in both approaches and consisted of three species: R. insidiosa, R. solanacearum and Ralstonia sp. These findings were concordant with previous studies, which reported that these species were abundant and isolated from water, soil, and clinical samples (Ryan et al, 2006;Patton et al, 2009;Lim and Lee, 2017). Ralstonia possesses both chemoautotrophic and photoautotrophic properties and also plays a role in nitrogen fixation by oxidising ammonium to produce nitrite, making it available for various types of plants and benefitting the ecosystem (Lim and Lee, 2017).…”
Section: P R E S S Table 4 List Of Bacterial Species Identified Fromsupporting
confidence: 92%
“…In the present study, the genus Ralstonia (class Betaproteobacteria) was detected in both approaches and consisted of three species: R. insidiosa, R. solanacearum and Ralstonia sp. These findings were concordant with previous studies, which reported that these species were abundant and isolated from water, soil, and clinical samples (Ryan et al, 2006;Patton et al, 2009;Lim and Lee, 2017). Ralstonia possesses both chemoautotrophic and photoautotrophic properties and also plays a role in nitrogen fixation by oxidising ammonium to produce nitrite, making it available for various types of plants and benefitting the ecosystem (Lim and Lee, 2017).…”
Section: P R E S S Table 4 List Of Bacterial Species Identified Fromsupporting
confidence: 92%
“…3C and 4C). Surprisingly, compared to elders with AD, elders with other dementia types had higher proportions of some opportunistic pathogens, including Ralstonia pickettii and Ralstonia mannitolilytica (33, 34), as well as B. fragilis, the most commonly isolated anaerobic pathogen (35).…”
Section: Resultsmentioning
confidence: 98%
“…bReferences for R . mannitolilytica 3–5,17,21,2630. cOne strain was resistant to piperacillin and susceptible to piperacillin/tazobactam.…”
Section: Discussionmentioning
confidence: 99%